Procesos metodológicos para la masificación del fútbol en los 8vos grados de educación general básica del colegio La Dolorosa, de la ciudad de Loja - Achupallas Ramón, Willan Alexander (2016)
This research work whose title is methodological processes for mass football in the 8th grades of basic general education school "La Dolorosa" city of Loja, aims to create methodological strategies based on recreational activities for disseminating this discipline, with the overall objective to determine whether the application of methodological processes encourage and enable amass practice football youth aged 12 to 14 years of Vicente Anda Aguirre Education Unit Section Diurna "La Dolorosa". ways that favor the inclusion of an effective strategy applied to young people considering their ages to motor, cognitive, emotional and social level, occupying free time and away from negative situations such as alcohol and drugs arises. To implement the project used methods such as: inductive - deductive, logical and historical modeling that are within the quantitative and qualitative research approach, the empirical evidence is based on field work with the support of different instruments including survey both teachers and students who allowed us to collect data. Consequently football practice positively affects the normal development of young people, both in the physical, psychological and social, manifested in their behavior inside and outside their environment. Taking a recommendation innovate methodological strategies for teaching soccer because that way you can facilitate teaching and learning in students and get a crowd giving way to the popularization of this sport.